Synthesis and characterization of acrylic fatty acid derivative and use as reactive coalescing agent - Joana V. Barbosa (2012)
A novel reactive coalescing agent based on vegetable oils is described. This conjugated acrylic fatty acid derivative (AcFAD) was synthesized by esterification of conjugated fatty acids (CFAs) with ethylene glycol, followed by reaction with acryloyl chloride. The reactions were monitored by monitoring the acid value and by IR spectroscopy. GCMS and NMR were used to obtain complete spectroscopic characterization of AcFAD. The potential of this conjugated derivative as reactive coalescing agent for waterborne acrylic resin formulations was evaluated in terms of drying times, minimum film forming temperatures and solvent rubbing resistance. Significant performance improvement was observed in all tests when AcFAD was added to acrylic resin, indicating occurrence of crosslinking of conjugated double bonds upon exposure to atmospheric oxygen (i.e. oxidative cure behaviour). On the other hand, CFAs addition to acrylic resin did not enhance drying behaviour or rubbing resistance of the dry films, despite the presence of conjugated double bonds as in AcFAD. This shows that introduction of (2-acryloyloxy)ethyl function plays an important role in insuring compatibility of the additive with the resin.